Literature Review on Impact of the COVID-19 Pandemic to Student Learning in Elementary and High School - Shi Han; Xiaopan Wang (CV TOPAZART, 2022)
The COVID-19 pandemic of 2020 has brought much challenge and disruption to the lives of students in elementary through high schools, their families, and their communities. The majority of participants were students, with other participants being teachers, parents, and various community members. Participants were interviewed on reactions to the pandemic experience, positive and negative life experiences both before the pandemic and during the panding that influenced coping, and reflections on what their local schools were doing to facilitate educational functtio Interview responses aligned with research already published on student experience with the pandemic and also produced new insight for future endeavors by the educational community in promotion of development of protective factors before si